Factors that Influence Customers’ Intention to Visit Green Hotels in Malaysia - Kartini Muniandy; Suzari Abdul Rahim; Aidi Ahmi; Nor Aida Abdul Rahman (International Journal of Supply Chain Management, 2019)
In recent years, the hospitality Industry has overcome numerous challenges to initiate green practices. Greater interest in customers green behaviours has led the hotel industry to practice more environmentally friendly activities. Therefore, this study aims to identify the factors that influence customers in visiting green hotels in Malaysia. The theory of planned behaviour (TPB) has been embedded to investigate the factors. Data was collected via questionnaires through online by invitation through email and offline from travellers in selected airports. IBM SPSS Statistics software was used to analyse the data. The results discovered that attitude, subjective norms, perceived behavioural control and environmental concern significantly influence customers in visiting green hotels. Meanwhile, attitudes mediate subjective norms and perceived behavioural control and finally attitudes, and perceived behavioural control possess a positive relationship with the environmental concern of visitors in visiting green hotels. Findings from this research can help the Malaysian government and hoteliers to integrate the research framework in their current business model and imposed more effective strategies on a green environment in developing green hotels.